Mutational studies on microbial xylanase: A review - NIDHI MATHUR,; AMERENDRA NATH PATHAK, (International Journal of Pharma and Bio Sciences, 2017)
The market for the utilization of enzymes by the industry has grown exponentially. Among the various classes of enzymes Xylanase is also utilized by various industries including paper and pulp industry, in production of various chemicals and products as rayon, cellophane, acetates, nitrates, methyl and ethyl cellulose, all produced from pulp and purification of the lignocellulosic material. The industrial application of Xylanase is found mainly in bio-industries, which require them to be stable at varied range of temperature and pH. As per the demand of industry there has been an increase in commercial xylanase preparations launched by various enzyme manufacturers. But these commercially available Xylanase lack the properties needed by the industries. To overcome those drawbacks work is in progress to design various mutants which can match the demand of the industries. The review is a compilation of various modified, mutants designed with the effect of modified residues have on the activity, stability and conformational changes. Various modifications have been made and their effects have been deliberated, but the obligation is to design mutants which are industry ready, tailor made Xylanase which possesses properties as compelled by processes.